A Literature Review in Wireless Sensor Hole Detection Along with Node Scheduling Algorithm - Tyagi, Somil; Kaur, Jaspreet (International Journal of Computer Sciences and Engineering, 2025)
A sensor network consist of low battery power, low cost, limited storage, tiny sensing devices. The one of the significant challenge in wireless sensor network is how well the network is monitored while maximizing network’s lifetime. Since sensing and transmitting data consume sensors’ energy, so to preserve energy an optimal sensor node scheduling scheme is required where only an optimal number of sensors are activate and other node are eligible to shut down to save their energy which can be used to prolong lifetime of sensor network. In this paper we introduced a node scheduling scheme which is based on optimal Coverage Preserving Scheme (OCoPS) that first check the redundant sensor and then decide to turn itself off. Further, in wireless sensor network there may exist some regions where sensors are not able to sense data or communicate which are called hole regions. Since hole region may jeopardize sensing, communicating or connectivity of sensor network, therefore identification of hole regions is also prime concern. In this paper, we first detect the hole regions in sensor network and then deploying sensors at appropriate location for covering that region. Our hole detection approach is based on Boundary Critical Points. The simulation results demonstrate that the proposed algorithm can lead to a high coverage ratio while keeping long network’s life.